Pengaruh Idealisme Dan Relativisme Pada Persepsi Mahasiswa Akuntansi Atas Perilaku Tidak Etis Akuntan - Hendra Tanjung; Andri Indrawan (Jurnal EBI, 2022)
This study aims to investigate the effect of idealism and relativism on accounting students' perceptions of accountants' unethical behavior. This research is important because the accounting profession is the guardian of public trust and accounting students are prospective accountants. The research was conducted using a survey technique with accounting students as respondents from a religion-based university. The prepared questionnaire was sent to accounting student respondents and the data that was successfully obtained through a questionnaire and met the requirements was then processed using SPSS 24 software. The quality of the data was determined through a series of tests such as normality and classical assumptions. The hypothesis was tested by multiple regression. The test results partially or simultaneously show that idealism and relativism affect accounting students' perceptions of accountants' unethical behavior. Therefore, universities as printers of the next generation need to provide learning that is able to improve and maintain idealism and foster relativism that is positive or in accordance with applicable norms. Providing learning about moral ethics and adding religious learning can be one solution. Key words: idealism, relativism, accountants, perception, ethics